Mating Status of an Herbivorous Stink Bug Female Affects the Emission of Oviposition-Induced Plant Volatiles Exploited by an Egg Parasitoid - Salerno, Gianandrea; Frati, Francesca; Conti, Eric; Peri, Ezio; Colazza, Stefano; Cusumano, Antonino (Frontiers in Physiology, 2019)
Insect parasitoids are under selection pressure to optimize their host location strategy in order to maximize fitness. In parasitoid species that develop on host eggs, one of these strategies consists in the exploitation of oviposition-induced plant volatiles (OIPVs), specific blends of volatile organic compounds released by plants in response to egg deposition by herbivorous insects. Plants can recognize insect oviposition via elicitors that trigger OIPVs, but very few elicitors have been characterized so far. In particular, the source and the nature of the elicitor responsible of egg parasitoid recruitment in the case of plants induced with oviposition by stink bugs is still unknown. In this paper, we conducted behavioural and molecular investigations to localize the source of the elicitor that attracts egg parasitoids and elucidate the role of host mating in elicitation of plant responses. We used as model study organisms a tritrophic system consisting of the egg parasitoid Trissolcus basalis, the stink bug host Nezara viridula and the plant Vicia faba. We found that egg parasitoid attraction to plant volatiles is triggered by extracts coming from the dilated portion of the stink bug spermathecal complex. However, attraction only occurs if extracts are obtained from mated females but not from virgin ones. Egg parasitoid attraction was not observed when extracts coming from the accessory glands (mesadene and ectadene) of male hosts were applied, either alone or in combination to plants. SDS-PAGE electrophoresis correlated with olfactometer observations as the protein profile of the dilated portion of the spermathecal complex was affected by the stink bug mating status suggesting post–copulatory physiological changes in this reproductive structure. This study contributed to better understanding the host location process by egg parasitoids and lay the basis for the chemical characterization of the elicitor responsible for OIPV emission.